Modified lithium iron manganese phosphate positive electrode material as well as preparation method and application thereof

Through the doping and carbon coating technology of rare earth elements Yb or Eu, the Jahn-Teller effect of lithium manganese iron phosphate positive electrode material is suppressed, and the problem of insufficient electrochemical performance and cycle stability at high magnification is solved, and a higher The discharge specific capacity and capacity retention rate improve the thermal stability and safety performance of the material.

CN119208578AActive Publication Date: 2024-12-27TIANJIN UNIV

Patent Information

Application Number
CN202411698083.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-27
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate cathode materials show insufficient electrochemical performance and cycle stability at high magnifications, especially the structural distortion and capacity attenuation problems caused by the Jahn-Teller effect are difficult to effectively suppress.

Method used

Through the doping and carbon coating technology of rare earth elements Yb or Eu, the electrochemical environment of Mn3+ electron cloud in MnO6 octahedral is adjusted to reduce Jahn-Teller distortion, and improve the rate performance and cycle stability of the material.

Benefits of technology

It achieves higher discharge specific capacity and excellent capacity retention at high magnification, improves the thermal stability and safety performance of the material, while avoiding the occurrence of side reactions, simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208578A_ABST
    Figure CN119208578A_ABST
Patent Text Reader

Abstract

The invention provides a modified lithium iron manganese phosphate positive electrode material as well as a preparation method and application thereof, and belongs to the field of electrodes and lithium ion batteries. The modified lithium manganese iron phosphate positive electrode material is carbon-coated modified lithium manganese iron phosphate, the modified lithium manganese iron phosphate is LiMn < 0.6 > Fe < 0.4-x > M < x > PO4, x is more than or equal to 0.005 and less than or equal to 0.02, and M is Yb or Eu.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the fields of electrodes and lithium-ion batteries, and particularly relates to a modified lithium manganese iron phosphate cathode material, a preparation method and an application thereof, and more specifically relates to a modified lithium manganese iron phosphate cathode material, a preparation method thereof, a positive electrode sheet using the modified lithium manganese iron phosphate cathode material, and a lithium-ion battery. Background Art

[0002] As an efficient energy storage and conversion device, lithium-ion batteries are widely used in the new energy field.

[0003] Compared with traditional layered cathode materials (such as lithium cobaltate and lithium nickelate), lithium iron phosphate (LiFePO4) has the advantages of strong thermal stability, high safety performance, no precious metals except lithium, and low price. Therefore, LiFePO4 cathode materials are widely used as positive electrode sheets of lithium-ion batteries and their market share increases year by year. However, the LiFePO4 cathode material has disadvantages such as low energy density and poor low-temperature performance, which also restricts its further application.

[0004] To further develop higher-performance cathode materials, the research on lithium manganese phosphate (LiMnPO4) cathode materials with the same olivine structure as LiFePO4 (capacity retention rate is nearly 48% at -20 °C low temperature) was started. The LiMnPO4 cathode material has excellent low-temperature performance (capacity retention rate is nearly 80% at -20 °C low temperature) and a high voltage platform of ~4.1V, and the theoretical energy density is as high as 701 Wh / kg, which is about 20% higher than that of LiFePO4. Therefore, in order to improve the electrochemical performance of LiFePO4, it was proposed to partially replace the Fe element in the lattice of the LiFePO4 cathode material with manganese (Mn) element to obtain a lithium manganese iron phosphate (LiMn 1-y Fe y PO4, 0 < y < 1) cathode material. This cathode material combines the advantages of LiFePO4 and LiMnPO4 and has greater development potential in the field of lithium-ion batteries in the future. However, for the LiMn 1-y Fe y PO4 cathode material, due to the double degeneracy of the outermost electron layer e 3+ orbital of Mn g the electron cloud system of Mn 3+ is in a metastable state, resulting in the structural disorder of MnO6 and the Jahn-Teller effect, which easily causes lattice mismatch and structural distortion of the LiMn 1-y Fe y PO4 cathode material, thereby leading to poor rate performance and cycle stability of the material, especially significant capacity attenuation occurs during charge and discharge at high rates (10.0C).

[0005] In order to inhibit the LiMn 1-y Fe y The Jahn-Teller effect of PO4 positive electrode materials improves their stability. Currently, strategies such as surface carbon coating, particle nano-sizing and metal ion doping have been proposed to regulate and modify the materials. However, these strategies are difficult to simultaneously meet the requirements of higher electrochemical performance and cycle stability at higher rates. Summary of the invention

[0006] In view of this, the present invention proposes a modified lithium manganese iron phosphate positive electrode material and a preparation method and application thereof, in order to at least partially solve the above technical problems. Therefore, the technical solution provided by the present invention is as follows.

[0007] As a first aspect of the present invention, a modified lithium iron manganese phosphate positive electrode material is provided, wherein the modified lithium iron manganese phosphate positive electrode material is a carbon-coated modified lithium iron manganese phosphate, wherein the modified lithium iron manganese phosphate is LiMn 0.6 Fe 0.4-x M x PO4, 0.005≤x≤0.02, M is Yb or Eu.

[0008] As a second aspect of the present invention, a method for preparing a modified lithium iron manganese phosphate positive electrode material is provided, comprising: providing FePO4 nanoparticles; mixing a solvent, FePO4 nanoparticles, a lithium source, a manganese source, a phosphorus source, a carbon source and an M source by ball milling to form a slurry, wherein the M source is a Yb source or a Eu source; the slurry is dried, ground and sieved to obtain a powder; in an inert atmosphere, the powder is calcined in stages to obtain a modified lithium iron manganese phosphate positive electrode material, wherein the modified lithium iron manganese phosphate positive electrode material is a carbon-coated modified lithium iron manganese phosphate.

[0009] As a third aspect of the present invention, a positive electrode sheet is provided, which is composed of a positive electrode collector and a positive electrode slurry coated and solidified on the surface of the positive electrode collector, wherein the positive electrode slurry includes the above-mentioned modified lithium manganese iron phosphate positive electrode material, a conductive material, a binder and an organic solvent.

[0010] As a fourth aspect of the present invention, a lithium-ion battery is provided, wherein the lithium-ion battery adopts the above-mentioned positive electrode sheet.

[0011] In the embodiment of the present invention, the unique non-spherical flexible 4f electron orbits and the tendency to absorb external localized electrons of Yb or Eu rare earth metal ions are used to adjust the MnO6 octahedron. 3+ The electrochemical environment of the electron cloud reduces the LiMn 0.6 Fe 0.4-x M xPO4, thereby reducing the structural distortion of the positive electrode material, a Yb or Eu rare earth element doped carbon-coated lithium manganese iron phosphate positive electrode material with higher rate performance and excellent cycle stability is designed. The present invention uses a solid phase mixing method to utilize rare earth element doped carbon-coated lithium manganese iron phosphate (LiMn 1- y Fe y PO4), obtain modified lithium manganese iron phosphate positive electrode material (LiMn 0.6 Fe 0.4-x M x PO4, 0.005≤x≤0.02, M is Yb or Eu). The present invention improves the electronic conductivity of the modified lithium manganese iron phosphate positive electrode material by carbon coating and rare earth element doping, and the carbon coating can effectively avoid direct contact between the positive electrode and the electrolyte, reduce the occurrence of some side reactions, and improve its cycle stability.

[0012] In the embodiment of the present invention, spherical FePO4 nanoparticles with high dispersibility and uniform particle size distribution are used as the synthetic modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.4-x M x The iron source precursor of lithium manganese iron phosphate (LMP4) positive electrode material is obtained by mixing FePO4 nanoparticles with lithium source, manganese source, phosphorus source, carbon source, Yb or Eu rare earth metal, and calcining to obtain a spherical, uniformly carbon-coated modified lithium manganese iron phosphate positive electrode material. The method for synthesizing the positive electrode material is relatively simple and can be prepared in batches. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a scanning electron microscope (SEM) image of the FePO4 nanoparticles in Example 1 of the present invention;

[0014] Figure 2 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 X-ray diffraction (XRD) pattern of PO4-S1 cathode material;

[0015] Figure 3 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 SEM image of PO4-S1 cathode material;

[0016] Figure 4 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 Cyclic stability diagram of PO4-S1 positive electrode sheet after 500 cycles at 5.0C;

[0017] Figure 5 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 Cyclic stability diagram of PO4-S1 positive electrode sheet after 500 cycles at 10.0C;

[0018] Figure 6 LiMn in Example 5 of the present invention 0.6 Fe 0.39 Yb 0.01 SEM image of PO4-S5 cathode material;

[0019] Figure 7 LiMn in Comparative Example 1 0.6 Fe 0.4 SEM image of PO4-S6 cathode material;

[0020] Figure 8 This is the SEM image of FePO4 nanoparticles in Comparative Example 2. DETAILED DESCRIPTION

[0021] Below, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of embodiments of the present invention. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of concepts of the present invention.

[0022] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0023] In the case of using expressions such as "at least one of A, B, and C, etc.", generally, it should be interpreted according to the meaning that those skilled in the art usually understand this expression (for example, "a system having at least one of A, B, and C" should include, but not be limited to, a system having only A, only B, only C, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", generally, it should be interpreted according to the meaning that those skilled in the art usually understand this expression (for example, "a system having at least one of A, B, or C" should include, but not be limited to, a system having only A, only B, only C, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.).

[0024] To suppress the Jahn-Teller effect of the LiMn 1-y Fe y PO4 (0 < y < 1) cathode material and improve its stability, currently, strategies such as surface carbon coating, particle nanosizing, and metal ion doping are proposed to regulate and modify the material, but there are some problems with these strategies.

[0025] For example: In the prior art, lithium iron phosphate doped with rare earth elements (any one of La, Ce, Pr, Tb, Sm) and carbon-coated is used to improve the lattice defects of the cathode material, and the stability of the crystal structure of the cathode material is improved. Although the cycling stability of the obtained cathode material has a certain improvement at a low rate (0.1C), the discharge specific capacity is relatively low, that is, the discharge specific capacity at 0.1C is only 116 - 120.0 mAh / g.

[0026] For example: Using metal ions (any one of Ti, Mg, V) to dope lithium iron phosphate with secondary carbon coating, through the strategy of ion doping modification combined with secondary carbon coating, the electron and ion transport efficiency between material particles is optimized, but the discharge specific capacity of this cathode material is still poor at a relatively high rate.

[0027] For another example: Using manganese element to dope and modify the lithium iron phosphate material to obtain a carbon-coated modified lithium manganese iron phosphate cathode material. By utilizing the synergistic effect of the gradient distribution of manganese, carbon, and iron elements, while reducing manganese loss, the electron conductivity is enhanced. However, the discharge specific capacity of this cathode material at 1.0C is 126.1 - 142 mAh / g, and the preparation process of this cathode material is relatively cumbersome, and dispersants and complexing agents are also added, with complex subsequent processing and high production costs.

[0028] Another example: In the prior art, there are also modified lithium manganese iron phosphate positive electrode materials doped with different elements (at least one of La and Al). By bulk doping, the Li-O bond is extended and vacancies are formed, which is convenient for Li + Migration and stabilization of material structure improve electrochemical performance. However, the discharge capacity and capacity retention rate of the prepared positive electrode material at a low rate of 1.0C need to be further improved.

[0029] Another example: the cathode material obtained by doping modified lithium manganese iron phosphate with at least one metal element among Ti, V, Ni, and Mg, wherein the prepared manganese iron hydroxide is mainly in the form of burred particles, and the particles are tightly connected internally, which can effectively alleviate the problem of easy breakage of spherical particles during sintering, thereby making the prepared cathode material have a higher energy density. Although the discharge specific capacity of the cathode material at low rate (1.0C) has been improved to a certain extent, such as the capacity retention rate of 80% to 91.5% after 100 cycles at 1.0C, the discharge specific capacity is low at higher rates, and the capacity retention rate is low after long cycles.

[0030] Another example: carbon-coated lithium manganese iron phosphate positive electrode material, by adding a modifier during the pretreatment of the slurry to promote the self-assembly of the raw materials to form a precursor, and at the same time coating the surface of the precursor with carbon, thereby improving the conductivity of the lithium manganese iron phosphate material. Although the prepared positive electrode material has a good improvement in conductivity, the battery rate performance and cycle performance still need further verification.

[0031] Another example: using fluorine-doped lithium manganese iron phosphate positive electrode materials with amorphous carbon and graphene coated on the surface, by constructing a conductive network and doping F ions to form F-Mn chemical bonds, manganese loss is reduced, and conductivity and structural stability are improved. Although the prepared material has improved discharge capacity and battery capacity retention at a lower rate (0.1C), the performance is poor at a higher rate (>1.0C), and N,N-dimethylformamide is used as a solvent, which is not only expensive, but also easy to pollute the environment, and is not suitable for large-scale factory production.

[0032] Another example: By adjusting the particle size ratio of the material, lithium manganese iron phosphate positive electrode material is obtained. Although this positive electrode material has excellent discharge specific capacity at a lower rate (0.1C), its electrochemical performance at a high rate (10.0C) needs to be further improved, and the battery cycle stability also needs further exploration.

[0033] Another example: In the prior art, lithium manganese iron phosphate is grown in situ on the surface of conductive carbon microspheres to form a three-dimensional conductive network to improve the conductivity of the material, and freeze-drying technology is used to stabilize the material structure to prepare lithium manganese iron phosphate positive electrode material. Although the positive electrode material prepared by this method has an improved discharge capacity (128.5mAh / g) at a low rate (0.1C), the capacity (41.0mAh / g) at a high rate (10.0C) is severely attenuated, and the preparation process is complicated, which is not suitable for industrial application.

[0034] In view of the problem that it is difficult to simultaneously meet the electrochemical performance and cycle stability at high rates (10.0C) in the above-mentioned prior art, the present invention proposes to use rare earth element doped carbon-coated lithium manganese iron phosphate to obtain a modified lithium manganese iron phosphate positive electrode material. By utilizing the unique non-spherical flexible 4f electron orbits and the tendency to absorb external localized electrons of the rare earth elements Yb and Eu to weaken the structural distortion in the positive electrode material, the modified lithium manganese iron phosphate positive electrode material can obtain higher rate performance and cycle stability.

[0035] Specifically, as a first aspect of the present invention, the modified lithium manganese iron phosphate positive electrode material provided by the present invention is a carbon-wrapped modified lithium manganese iron phosphate, wherein the modified lithium manganese iron phosphate is LiMn 0.6 Fe 0.4-x M x PO4, 0.005≤x≤0.02, M is Yb or Eu.

[0036] In the embodiment of the present invention, Eu 3+ , Yb 3+ Rare earth metal ions have unique non-spherical flexible 4f electron orbitals, where the anisotropic shape of the 4f electron orbital electron cloud originates from the spin-orbit coupling caused by the staggered orbital energy levels of rare earth metal ions. 3+ , Yb 3+ The outermost electron layer in the rare earth metal ions has the characteristic of tending to absorb external localized electrons to achieve a more stable state of half-filled or fully filled electron layer. 3+ , Yb 3+ The non-spherical flexible 4f electron orbital characteristics of rare earth metal ions and their tendency to absorb external localized electrons are used to adjust the Mn in the MnO6 octahedron. 3+ The chemical environment of the electron cloud can reduce the 0.6 Fe 0.4-x M x Jahn-Teller distortion of PO4. The Jahn-Teller effect is significantly suppressed, thereby reducing the structural distortion of the positive electrode material, thereby obtaining a rare earth element-doped carbon-coated lithium manganese iron phosphate positive electrode material with higher rate performance and excellent cycle stability.

[0037] According to an embodiment of the present invention, the modified lithium manganese iron phosphate of the present invention has an olivine structure, wherein Fe is in a +2 valence state, and Mn and M (M is Yb or Eu) both have a +3 valence state. The modified lithium manganese iron phosphate with an olivine structure has the advantages of strong thermal stability, high safety performance, no precious metals except lithium, and low price.

[0038] According to an embodiment of the present invention, as a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned modified lithium iron manganese phosphate positive electrode material, comprising: providing FePO4 nanoparticles as an iron source; ball-milling and mixing a solvent, FePO4 nanoparticles, a lithium source, a manganese source, a phosphorus source, a carbon source and an M source to form a slurry, wherein the M source is a Yb source or a Eu source; the slurry is dried, ground and sieved to obtain a powder; in an inert atmosphere, the powder is calcined in stages to obtain a carbon-coated modified lithium iron manganese phosphate positive electrode material.

[0039] In an embodiment of the present invention, spherical FePO4 nanoparticles with high dispersibility, uniform particle size and uniform distribution are used as the iron source for synthesizing modified lithium iron manganese phosphate positive electrode materials, and then the FePO4 nanoparticles are mixed with a lithium source, a manganese source, a phosphorus source, a carbon source, and an M source (i.e., Yb or Eu rare earth elements) by ball milling. After calcination, a spherical, uniform particle size and uniform distribution carbon-coated modified lithium iron manganese phosphate positive electrode material can be obtained. The method for synthesizing the positive electrode material is relatively simple, no additional additives are used, the cost is low, the post-processing process is simple, and it can be prepared in batches.

[0040] According to an embodiment of the present invention, FePO4 nanoparticles are prepared by the following method: under oxidant conditions, an oxidation reaction is first carried out with a divalent iron salt and a phosphorus-containing solution, and then the pH of the reaction solution is adjusted to 1.5-1.8 with an alkali solution, and the reaction is carried out for 1-3 hours to obtain a FePO4 slurry, and the FePO4 slurry is calcined at 500-550°C for 2-3 hours to obtain FePO4 nanoparticles, wherein the phosphorus-containing solution includes a phosphate solution or a phosphoric acid solution. The divalent iron salt is selected from FeSO4·7H2O, and for other Fe 2+ The divalent iron salt can also be used; the phosphate is selected from at least one of sodium phosphate and sodium dihydrogen phosphate; the alkali solution is selected from any one of NaOH and KOH, preferably NaOH. For example, the preparation of FePO4 nanoparticles includes: using pure water to dissolve the divalent iron salt (FeSO4·7H2O) as the base liquid, pouring the phosphoric acid solution into the base liquid under constant stirring, and using a constant pressure dropping funnel to drop a hydrogen peroxide solution to oxidize Fe 2+; Then, the temperature was raised to 80°C, and the pH was adjusted to 1.8 with NaOH solution. The reaction was carried out in an oil bath with constant stirring for 3 hours; Then, the slurry was filtered while hot to obtain FePO4 precipitate. Washing with pure water and filtering were repeated 5 times, and the product was dried and calcined to obtain white FePO4 nanoparticles.

[0041] According to an embodiment of the present invention, the lithium source is selected from at least one of Li2CO3, LiOH, LiNO3, LiCl, and CH3COOLi; the manganese source is selected from at least one of MnCO3, Mn3(PO4)2, MnHPO4, Mn(H2PO4)2, Mn(CH3COO)2, Mn(NO3)2, MnSO4, MnC2O4, and MnCl2; the phosphorus source is selected from at least one of H3PO4, Fe3(PO4)2, FePO4, (NH4)2HPO4, NH4H2PO4, (NH4)3PO4, Li3 PO4, LiH2PO4; the carbon source is selected from at least one of glucose, sucrose, fructose, soluble starch, citric acid, amino acid, dextrin, polyvinyl pyrrolidone, and polyethylene glycol; the Yb source is selected from any one of Yb2O3, Yb(CH3COO)3·4H2O, YbCl3, Yb2(SO4)3, and Yb(NO3)3·5H2O; the Eu source is selected from any one of Eu2O3, Eu(CH3COO)3·4H2O, EuCl3, Eu2(SO4)3, and Eu(NO3)3·6H2O.

[0042] According to an embodiment of the present invention, the ball milling mixing time is 6 to 15 hours, the rotation speed is 600 to 1000 rpm, and the ball-to-material ratio is 15 to 20:1. Within this ratio range, it is helpful to evenly mix the FePO4 nanoparticles, lithium source, manganese source, phosphorus source, carbon source and M source (i.e., Yb source or Eu source) by ball milling, so that the subsequent calcination can obtain a modified lithium manganese iron phosphate positive electrode material with a spherical shape, uniform particle size and uniform distribution.

[0043] According to an embodiment of the present invention, the powder is calcined in stages, including: first calcining the powder at 300-350°C for 2-6 hours, and then calcining the powder at 600-750°C for 10-15 hours. In the first stage of calcination, excess moisture in the powder is effectively removed to avoid particle breakage due to excessive temperature during calcination; in the second stage of calcination, excess impurities in the powder are removed and activation is performed at the same time.

[0044] According to an embodiment of the present invention, the present invention also provides a positive electrode sheet, which is composed of a positive current collector and a positive electrode slurry coated and cured on the positive current collector; the positive electrode slurry includes the above-mentioned modified lithium manganese iron phosphate positive electrode material, a conductive agent, a binder and an organic solvent. Among them, the positive current collector is selected from Al foil; the conductive agent is selected from any one of conductive carbon black (Super P), acetylene black, Ketjen black, and carbon nanotubes; the binder is selected from any one of polyvinylidene fluoride, polystyrene butadiene copolymer, sodium carboxymethyl cellulose, polyacrylic acid, polyvinyl alcohol, polyamide, polyethyleneimine, and polypyrrole; the organic solvent is selected from any one of N-methylpyrrolidone, dimethylformamide, and dimethyl sulfoxide.

[0045] In an embodiment of the present invention, a modified lithium manganese iron phosphate positive electrode material, a conductive agent, a binder and an organic solvent are mixed to form a positive electrode slurry, which is then coated on a positive electrode collector to form a positive electrode sheet. The obtained positive electrode sheet has high electrochemical performance.

[0046] According to an embodiment of the present invention, the present invention further provides a lithium-ion battery, which uses the positive electrode sheet in the above embodiment.

[0047] According to an embodiment of the present invention, the lithium-ion battery may be a button battery.

[0048] In an embodiment of the present invention, the modified lithium iron manganese phosphate positive electrode material provided by the present invention comprises a lithium ion battery having a higher discharge specific capacity and a better capacity retention rate at 0.1C~10.0C, especially at a high rate of 5.0C~10.0C.

[0049] In order to make the technical solution of the present invention clearer and more understandable, the technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings. It should be noted that the following specific embodiments are only examples.

[0050] Example

[0051] Example 1

[0052] Preparation of FePO4 nanoparticles: First, add 69.52g FeSO4·7H2O and 200mL pure water into a 1000mL three-necked flask to prepare a solution; then, add 30.00g H3PO4 solution with a mass concentration of 85% to the three-necked flask under magnetic stirring at a speed of 1000r / min. After the addition is completed, mix and stir for 2 minutes to obtain a mixed solution. Secondly, add 17.00g H2O2 with a mass concentration of 30% to the above mixed solution at a rate of 1 drop / second. Furthermore, under the condition of an 80℃ oil bath, 50mL NaOH solution with a concentration of 6.66mol / L is also added to the three-necked flask at a rate of 1 drop / second. After the addition is completed, continue to react for 3h; then, filter and separate while hot to obtain a solid FePO4 sample. Subsequently, use 500mL pure water, stir and wash for 3min at a speed of 200r / min, filter, and repeat the above washing process 3 times. Finally, the anhydrous FePO4 nanoparticles were obtained by calcining at 550 °C in a tube furnace for 3 h in air atmosphere.

[0053] Figure 1 This is a scanning electron microscope (SEM) image of the FePO4 nanoparticles in Example 1 of the present invention.

[0054] like Figure 1 As shown, the FePO4 nanoparticles synthesized by the method in Example 1 have a regular spherical morphology, a smooth surface, and a uniform particle size and distribution.

[0055] Preparation of modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S1, i.e. LMFP-1%Yb) cathode material: The FePO4 nanoparticles (iron source), Li2CO3, MnCO3, LiH2PO4, Yb(CH3COO)3·4H2O and glucose prepared above were weighed to 11.90g, 3.37g, 13.97g, 12.63g, 0.71g and 10.65g, respectively, and mixed evenly with 66.54mL of distilled water in a 500mL beaker. Then, the ball-to-material ratio was 15:1 (the ratio of grinding balls to materials was 15:1), and the ball milling was carried out at 800rpm for 12h. After ball milling, the precursor sample was obtained by air drying at 80℃ for 12h and dry grinding at 1000rpm for 20min. Finally, the precursor sample was placed in a tube furnace and calcined at 350 °C for 4 h under nitrogen atmosphere and then at 670 °C for 12 h to obtain LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S1 positive electrode material.

[0056] Figure 2 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 X-ray diffraction (XRD) pattern of PO4-S1 positive electrode material.

[0057] like Figure 2 As shown, the LiMn synthesized in Example 1 0.6 Fe 0.39 Yb 0.01 The XRD spectrum of the PO4-S1 cathode material sample is similar to the spectrum and diffraction data of the lithium iron manganese phosphate standard card (PDF#13-0336), with a sharp peak, indicating that the cathode material has good crystallinity, and no other impurity peaks are observed in the spectrum, indicating that the LiMn prepared by the method provided by the present invention 0.6 Fe 0.39 Yb 0.01 The PO4-S1 cathode material is pure phase LMFP.

[0058] Figure 3 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 SEM image of PO4-S1 positive electrode material.

[0059] like Figure 3 As shown, the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 The particle size distribution of PO4-S1 positive electrode material is uniform and the dispersion is good.

[0060] Preparation of LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S1 positive electrode sheet: First, weigh 0.1g of polyvinylidene fluoride (PVDF) as a binder and add it to a weighing bottle. Then, add 1.5mL of N-methylpyrrolidone (NMP) organic solvent to the weighing bottle and stir magnetically at 1000rpm / min for 2h. Then, add 0.8g of the prepared LiMn 0.6 Fe 0.39 Yb 0.01PO4-S1 positive electrode material, 0.1g conductive agent (Super P) and 2mL NMP were added to the above weighing bottle and magnetically stirred at 1000rpm / min for 4h to obtain positive electrode slurry. Subsequently, the positive electrode slurry was evenly coated on the aluminum foil using a coating machine at a coating speed of 25mm / s, and the coating thickness was 150μm. Then, the coated aluminum foil was placed in a 60℃ forced air drying oven for 4h; thereafter, it was sliced ​​and dried in a vacuum oven at 110℃ for 12h to obtain LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S1 positive electrode sheet.

[0061] Assemble button cells: In a glove box, 0.6 Fe 0.39 Yb 0.01 The PO4-S1 positive electrode sheet is the working electrode, metallic lithium is the counter electrode, Celgard2400 is the separator, and 1 mol / L LiPF6 / EC:DEC:DMC (volume ratio 1:1:1) is the electrolyte, which are assembled into a CR2032 button battery.

[0062] The button cell was tested for charge and discharge performance. The specific test process was as follows: at room temperature and constant current conditions, the test voltage range of rate performance was 2.5V to 4.5V, the charge and discharge rate was 0.1C for 3 cycles, 0.2C, 0.5C, 1.0C, 2.0C, 5.0C, 10.0C for 5 cycles each, and then back to 0.1C for 5 cycles. The specific test results are shown in Table 1.

[0063] After testing, it can be seen from Table 1 that LiMn 0.6 Fe 0.39 Yb 0.01 The PO4-S1 positive electrode sheet has a first discharge specific capacity of 155.80 mAh / g at 0.1C; the first discharge specific capacity at 0.2C is 153.76 mAh / g; the first discharge specific capacity at 0.5C is 150.75 mAh / g; the first discharge specific capacity at 1.0C is 146.14 mAh / g; the first discharge specific capacity at 2.0C is 143.45 mAh / g; the first discharge specific capacity at 5.0C is 135.32 mAh / g; and the first discharge specific capacity at 10.0C is 127.73 mAh / g.

[0064] Furthermore, the LiMn 0.6 Fe 0.39 Yb 0.01 The battery composed of PO4-S1 positive electrode sheet was tested for cycle stability at different rates. The specific test results Figure 4-Figure 5 And as shown in Table 2.

[0065] Figure 4 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 Cyclic stability diagram of PO4-S1 positive electrode sheet after 500 cycles at 5.0C; Figure 5 LiMn in Example 1 of the present invention 0.6 Fe 0.39 Yb 0.01 Cycling stability diagram of PO4-S1 positive electrode sheet after 500 cycles at 10.0C.

[0066] like Figure 4 As shown in Figure 2, after 500 cycles at 5.0C, the battery capacity retention rate is 93.32%; Figure 5 As shown in the figure, after 500 cycles at 10.0C, the battery capacity retention rate is 93.44%. 0.6 Fe 0.39 Yb 0.01 The PO4-S1 cathode material has a high rate performance at a low rate (0.1C), no obvious attenuation of specific capacity at 5.0C, and stable electrochemical performance at a high rate (10.0C).

[0067] Example 2

[0068] Preparation of FePO4 nanoparticles: First, add 69.52g FeSO4·7H2O and 200mL pure water into a 1000mL three-necked flask to prepare a solution; then, add 30.00g H3PO4 solution with a mass concentration of 85% to the three-necked flask under magnetic stirring at a speed of 1000 r / min. After the addition is completed, mix and stir for 2 minutes to obtain a mixed solution. Secondly, add 17.00g H2O2 with a mass concentration of 30% to the above mixed solution at a rate of 1 drop / second; furthermore, under the condition of an 80℃ oil bath, add 50mL NaOH solution with a concentration of 6.66mol / L to the three-necked flask at the same rate of 1 drop / second. After the addition is completed, continue to react for 3h. Then, filter and separate while hot to obtain a FePO4 solid sample, and use 500mL pure water to stir and wash for 3min at a speed of 200r / min, then filter and repeat the above washing process 3 times. Finally, the anhydrous FePO4 nanoparticles were obtained by calcining at 550 °C in a tube furnace for 3 h in air atmosphere.

[0069] Preparation of modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.395 Yb 0.005PO4-S2) Positive electrode material: Weigh the masses of the FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4, Yb(CH3COO)3·4H2O and glucose prepared above to be 12.01g, 3.37g, 13.97g, 12.63g, 0.35g and 10.65g respectively, and mix them evenly with 66.54mL distilled water in a 500mL beaker. Then, with a ball-to-material ratio of 15:1, ball milling was performed at 800rpm for 12h. After ball milling, the precursor sample was obtained by forced air drying at 80°C for 12h and dry milling at 1000rpm for 20min. Finally, the precursor sample was placed in a tubular furnace and calcined at 350°C for 4h under nitrogen atmosphere protection, and then calcined at 670°C for 12h to obtain LiMn 0.6 Fe 0.395 Yb 0.005 PO4-S2 positive electrode material.

[0070] Preparation of LiMn 0.6 Fe 0.395 Yb 0.005 PO4-S2 positive electrode sheet: First, weigh 0.1g of polyvinylidene fluoride (PVDF) as a binder and add it to a weighing bottle. Then, add 1.5mL of N-methylpyrrolidone (NMP) organic solvent to the weighing bottle and stir magnetically at 1000rpm / min for 2h. Then, add 0.8g of the prepared LiMn 0.6 Fe 0.395 Yb 0.005 PO4-S2 positive electrode material, 0.1g Super P and 2mL NMP were added to the above weighing bottle and magnetically stirred at 1000rpm / min for 4h to obtain positive electrode slurry. Subsequently, the positive electrode slurry was evenly coated on the aluminum foil using a coating machine at a coating speed of 25mm / s, and the coating thickness was 150μm. Then, the coated aluminum foil was placed in a 60℃ forced air drying oven for 4h; thereafter, it was sliced ​​and dried in a vacuum oven at 110℃ for 12h to obtain LiMn 0.6 Fe 0.395 Yb 0.005 PO4-S2 positive electrode sheet.

[0071] Assemble button cells: In a glove box, 0.6 Fe 0.395 Yb 0.005 The PO4-S2 positive electrode sheet is the working electrode, metallic lithium is the counter electrode, Celgard2400 is the separator, and 1 mol / L LiPF6 / EC:DEC:DMC (volume ratio 1:1:1) is the electrolyte, which are assembled into a CR2032 button battery.

[0072] The button cell was tested for charge and discharge performance. The specific test process was as follows: at room temperature and constant current conditions, the test voltage range of rate performance was 2.5V to 4.5V, the charge and discharge rate was 0.1C for 3 cycles, 0.2C, 0.5C, 1.0C, 2.0C, 5.0C, 10.0C for 5 cycles each, and then back to 0.1C for 5 cycles. 0.6 Fe 0.395 Yb 0.005 The battery composed of PO4-S2 positive electrode sheets was tested for cycle stability at different rates. The specific test results are shown in Tables 1 and 2.

[0073] After testing, it can be seen from Table 1 that LiMn 0.6 Fe 0.395 Yb 0.005 The PO4-S2 positive electrode sheet has a first discharge capacity of 155.12 mAh / g at 0.1C, 151.61 mAh / g at 0.2C, 148.65 mAh / g at 0.5C, 144.79 mAh / g at 1.0C, 140.22 mAh / g at 2.0C, 133.24 mAh / g at 5.0C, and 124.01 mAh / g at 10.0C. 0.6 Fe 0.395 Yb 0.005 The PO4-S2 positive electrode sheet has a battery capacity retention rate of 91.94% after 500 cycles at 5.0C and a battery capacity retention rate of 91.86% after 500 cycles at 10.0C.

[0074] Example 3

[0075] Preparation of FePO4 nanoparticles: Example 3 uses the same method as in Examples 1 and 2 to prepare anhydrous FePO4 nanoparticles.

[0076] Preparation of modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.38 Yb 0.02PO4-S3) Positive electrode material: Weigh the FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4, Yb(CH3COO)3·4H2O and glucose prepared above to be 11.60g, 3.37g, 13.97g, 12.63g, 1.42g and 10.65g respectively, and mix them evenly with 66.54mL distilled water in a 500mL beaker. Then, with a ball-to-material ratio of 15:1, ball milling was performed at 800rpm for 12h; after ball milling, the precursor sample was dried with air at 80℃ for 12h and dry-milled at 1000rpm for 20min to obtain the precursor sample. Finally, the precursor sample was placed in a tubular furnace and calcined at 350℃ for 4h under nitrogen atmosphere protection, and then calcined at 670℃ for 12h to obtain LiMn 0.6 Fe 0.38 Yb 0.02 PO4-S3 positive electrode material.

[0077] Example 3 LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.38 Yb 0.02 PO4-S3 positive electrode sheets were assembled into button cells for charge and discharge performance and battery cycle stability tests at different rates. The specific test process was the same as that of Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0078] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.38 Yb 0.02 The PO4-S3 positive electrode sheet has a first discharge capacity of 154.74 mAh / g at 0.1C, 151.19 mAh / g at 0.2C, 148.84 mAh / g at 0.5C, 145.88 mAh / g at 1.0C, 141.92 mAh / g at 2.0C, 133.99 mAh / g at 5.0C, and 125.99 mAh / g at 10.0C. 0.6 Fe 0.38 Yb 0.02 The PO4-S3 positive electrode sheet was cycled 500 times at 5.0C, and the battery capacity retention rate was 92.84%; after cycling 500 times at 10.0C, the battery capacity retention rate was 93.17%.

[0079] Example 4

[0080] Preparation of FePO4 nanoparticles: Example 4 uses the same method as in Examples 1 and 2 to prepare anhydrous FePO4 nanoparticles.

[0081] Preparation of modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.39 Eu 0.01 PO4-S4) positive electrode material: The masses of the FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4, Eu(CH3COO)3·4H2O and glucose prepared above were weighed to be 11.90g, 3.37g, 13.97g, 12.63g, 0.71g and 10.65g, respectively, and mixed evenly with 66.54mL of distilled water in a 500mL beaker. Then, with a ball-to-material ratio of 15:1, ball milling was performed at 800rpm for 12h; after ball milling, the precursor sample was dried at 80℃ for 12h and dry-milled at 1000rpm for 20min to obtain the precursor sample. Finally, the precursor sample was placed in a tubular furnace and calcined at 350℃ for 4h under nitrogen atmosphere protection, and then calcined at 670℃ for 12h to obtain LiMn 0.6 Fe 0.39 Eu 0.01 PO4-S4 positive electrode material.

[0082] LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.39 Eu 0.01 PO4-S4 positive electrode sheets were assembled into button cells for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing process was the same as in Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0083] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.39 Eu 0.01 The PO4-S4 positive electrode sheet has a first discharge capacity of 150.73mAh / g at 0.1C, 146.72mAh / g at 0.2C, 143.99mAh / g at 0.5C, 140.14mAh / g at 1.0C, 137.77mAh / g at 2.0C, 132.62mAh / g at 5.0C, and 124.52mAh / g at 10.0C. 0.6 Fe 0.39 Eu 0.01 The PO4-S4 positive electrode sheet was cycled 500 times at 5.0C, and the battery capacity retention rate was 93.84%; after cycling 500 times at 10.0C, the battery capacity retention rate was 93.10%.

[0084] Example 5

[0085] Preparation of FePO4 nanoparticles: FePO4 nanoparticles were prepared by the method provided by Chinese Patent Publication No. CN114477120A (a method for preparing iron phosphate). Specifically, 25 mL of FeSO4·7H2O solution was added to a 100 mL reactor, the temperature was raised to 40°C, stirred at 50 r / min, and the flow rate was 13 m 3 / h H3PO4 solution, after 3 hours of reaction, add excess H2O2 solution to the reaction system Fe 2+ Oxidized to Fe 3+ , oxidation reaction for 2h. After the reaction, adjust the pH of the reaction system to 4.2 with NH3·H2O solution to produce a milky white precipitate, then heat to 90℃ and continue stirring for 1.0h. After the reaction is completed, filter while hot; after filtration, put the solid into a 1000mL beaker, add 500ml pure water, and stir with an electric stirrer for 3min at a speed of 200r / min. This is the first filtration and washing. Then filter and wash again, and repeat this 5 times. After washing, transfer the solid to a large glass culture dish, put it in when the temperature of the blast drying oven reaches 60℃, and dry it at this temperature for 12h. Finally, put the sample into a quartz boat in a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min in an air atmosphere, and calcine it in a tube furnace at this temperature for 3h to obtain anhydrous FePO4 nanoparticles.

[0086] Preparation of modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S5) Positive electrode material: Weigh 3.37g, 11.90g, 13.97g, 12.63g, 0.71g, and 10.65g of Li2CO3, the above-mentioned FePO4 nanoparticles, MnCO3, LiH2PO4, Yb(CH3COO)3·4H2O, and glucose, respectively; then add 66.22mL of distilled water; with a ball-to-material ratio of 15:1, ball mill at 800rpm for 12h; then blow dry at 80℃ to evaporate all the water, dry mill at 1000rpm for 20min after evaporation; then sieve the powder with a 200-mesh standard sieve to obtain a precursor sample. The precursor powder was placed in a nitrogen atmosphere, first calcined at 350℃ for 4h, and then calcined at 670℃ for 12h to obtain LiMn 0.6 Fe 0.39 Yb 0.01 PO4-S5 positive electrode material.

[0087] Figure 6 LiMn in Example 5 of the present invention 0.6 Fe 0.39 Yb 0.01SEM image of PO4-S5 positive electrode material.

[0088] like Figure 6 As shown, the LiMn prepared in Example 5 0.6 Fe 0.39 Yb 0.01 The particle size of PO4-S5 cathode material is large, the dispersion is poor, and the agglomeration phenomenon is serious. This shows that the particle size and dispersion of FePO4 nanoparticle precursor will affect the particle size and distribution of cathode material.

[0089] Example 5 LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.39 Yb 0.01 PO4-S5 positive electrode sheets were assembled into button cells for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing process were the same as in Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0090] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.39 Yb 0.01 The PO4-S5 positive electrode sheet has an initial discharge capacity of 144.20 mAh / g at 0.1C, 142.72 mAh / g at 0.2C, 141.26 mAh / g at 0.5C, 139.95 mAh / g at 1.0C, 136.32 mAh / g at 2.0C, 121.26 mAh / g at 5.0C, and 106.47 mAh / g at 10.0C. 0.6 Fe 0.39 Yb 0.01 The PO4-S5 positive electrode sheet was cycled 500 times at 5.0C, and the battery capacity retention rate was 92.50%; after cycling 500 times at 10.0C, the battery capacity retention rate was 93.10%.

[0091] Comparative Example

[0092] Comparative Example 1

[0093] Preparation of FePO4 nanoparticles: In Comparative Example 1, anhydrous FePO4 nanoparticles were prepared using the same method as in Examples 1 and 2.

[0094] Preparation of lithium manganese iron phosphate (LiMn 0.6 Fe 0.4PO4-S6) Positive electrode material: Weigh the FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4 and glucose prepared above to 12.21g, 3.37g, 13.97g, 12.63g and 10.65g respectively, and mix them evenly with 66.54mL distilled water in a 500mL beaker. Then, with a ball-to-material ratio of 15:1, ball milling was performed at 800rpm for 12h; after ball milling, it was blown dried at 80℃ for 12h and dry milled at 1000rpm for 20min to obtain a precursor sample. The precursor sample was placed in a tubular furnace and calcined at 350℃ for 4h under nitrogen atmosphere protection, and then calcined at 670℃ for 12h to obtain LiMn 0.6 Fe 0.4 PO4-S6 positive electrode material.

[0095] Figure 7 LiMn in Comparative Example 1 0.6 Fe 0.4 SEM image of PO4-S6 positive electrode material.

[0096] like Figure 7 As shown, LiMn prepared in Comparative Example 1 0.6 Fe 0.4 The PO4-S6 positive electrode material particles are evenly distributed and have good dispersion.

[0097] Comparative Example 1 LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.4 PO4-S6 positive electrode sheets were assembled into button cells for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing process was the same as in Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0098] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.4 The PO4-S6 positive electrode sheet has a first discharge capacity of 156.15 mAh / g at 0.1C, 151.31 mAh / g at 0.2C, 146.53 mAh / g at 0.5C, 143.46 mAh / g at 1.0C, 138.67 mAh / g at 2.0C, 131.24 mAh / g at 5.0C, and 123.51 mAh / g at 10.0C. 0.6 Fe 0.4The PO4-S6 positive electrode sheet was cycled 500 times at 5.0C, and the battery capacity retention rate was 86.51%; after cycling 500 times at 10.0C, the battery capacity retention rate was 85.35%.

[0099] Comparative Example 2

[0100] FePO4 nanoparticles: FePO4 nanoparticles were synthesized using the method provided by Chinese Patent Publication No. CN114477120A (a method for preparing iron phosphate). Specifically, FePO4 nanoparticles were prepared by adding 25 mL of FeSO4·7H2O solution to a 100 mL reactor, heating to 40°C, stirring at 50 r / min, and adding a flow rate of 13 m 3 / h H3PO4 solution, after 3 hours of reaction, add excess H2O2 solution to the reaction system Fe 2+ Oxidized to Fe 3+ , oxidation reaction for 2h. After the reaction, adjust the pH of the reaction system to 4.2 with NH3·H2O solution to produce a milky white precipitate, then heat to 90℃ and continue stirring for 1.0h. After the reaction is completed, filter while hot; after filtration, put the solid into a 1000mL beaker, add 500ml pure water, and stir with an electric stirrer for 3min at a speed of 200r / min. This is the first filtration and washing. Then filter and wash again, and repeat this 5 times. After washing, transfer the solid to a large glass culture dish, put it in when the temperature of the blast drying oven reaches 60℃, and dry it at this temperature for 12h. Finally, put the sample into a quartz boat in a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min in an air atmosphere, and calcine it in a tube furnace at this temperature for 3h to obtain anhydrous FePO4 nanoparticles.

[0101] Figure 8 This is the SEM image of FePO4 nanoparticles in Comparative Example 2.

[0102] like Figure 8 As shown, the FePO4 nanoparticles synthesized by the method in Comparative Example 2 have irregular morphology, uneven particle size distribution, poor dispersibility, and serious agglomeration.

[0103] Preparation of lithium manganese iron phosphate (LiMn 0.6 Fe 0.4PO4-S7) Positive electrode material: Weigh the masses of iron phosphate FePO4, Li2CO3, MnCO3, LiH2PO4 and glucose in the above comparative example 2 to be 12.21g, 3.37g, 13.97g, 12.63g and 10.65g respectively, and mix them evenly with 66.54mL distilled water in a 500mL beaker. Then, with a ball-to-material ratio of 15:1, ball milling was performed at 800rpm for 12h; after ball milling, it was blown dried at 80℃ for 12h, and dry milled at 1000rpm for 20min to obtain a precursor sample. The precursor sample was calcined at 350℃ for 4h in a tubular furnace under nitrogen atmosphere protection, and then calcined at 670℃ for 12h to obtain LiMn 0.6 Fe 0.4 PO4-S7 positive electrode material.

[0104] Comparative Example 2 LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.4 PO4-S7 sample positive electrode sheets were assembled into button cells for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing process were the same as in Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0105] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.4 The PO4-S7 positive electrode sheet has a first discharge capacity of 144.85mAh / g at 0.1C, 143.05mAh / g at 0.2C, 141.92mAh / g at 0.5C, 137.50mAh / g at 1.0C, 131.15mAh / g at 2.0C, 118.46mAh / g at 5.0C, and 101.45mAh / g at 10.0C. 0.6 Fe 0.4 The PO4-S7 positive electrode sheet was cycled 500 times at 5.0C, and the battery capacity retention rate was 86.00%; after cycling 500 times at 10.0C, the battery capacity retention rate was 82.76%.

[0106] The above-mentioned comparative example 2 adopts a method for preparing FePO4 nanoparticles different from that of Example 1 of the present invention. The differences and advantages between the two are as follows.

[0107] (1) NaOH is used as a precipitant in Example 1, while NH3·H2O is used as a precipitant in Comparative Example 2. In the process of preparing FePO4 nanoparticles in Comparative Example 2, a large amount of toxic ammonium ions are introduced, causing serious pollution to the environment. The subsequent treatment process is relatively complicated and is not suitable for large-scale industrial production.

[0108] (2) In Example 1, NaOH solution was used to adjust the pH of the system to 1.8, while in Comparative Example 2, NH3·H2O solution was used to adjust the pH of the system to 4.2. The use of NH3·H2O solution to adjust the pH of the system is likely to cause some Fe to remain in the system. 3+ And converted into Fe(OH)3 precipitation, that is, Fe 3+ The conversion is incomplete.

[0109] (3) The temperature for preparing FePO4 nanoparticles in Example 1 is 80°C. The prepared FePO4 nanoparticles are spherical and regular in shape, with a smooth and delicate particle surface, consistent particle size and uniform dispersion. However, the temperature for preparing FePO4 nanoparticles in Comparative Example 2 is 90°C. Due to the high reaction temperature, the particle size distribution of the prepared FePO4 nanoparticles is uneven and there is obvious agglomeration.

[0110] Therefore, in the present invention, NaOH is preferably used as a precipitant and pH regulator for preparing FePO4 nanoparticles, and the pH of the system is adjusted to 1.8.

[0111] Comparative Example 3

[0112] Comparative Example 3 refers to Chinese patent publication number CN118231612A, which discloses a rare earth element (any one of La, Ce, Pr, Tb, Sm) doped lithium iron manganese phosphate / carbon-coated positive electrode material, and its preparation method and application. The La element with the best performance is selected to replace the Yb or Eu element to prepare the lithium iron manganese phosphate positive electrode material as a comparative example. The only difference is that the doping element in Example 1 is 1% Yb, while the doping element in this comparative example 3 is 1% La. That is, Comparative Example 3 provides a lanthanum (La) doped carbon-coated lithium iron manganese phosphate positive electrode material, and its preparation method and application, and the specific process is as follows.

[0113] Preparation of FePO4 nanoparticles: In Comparative Example 3, anhydrous FePO4 nanoparticles were prepared using the same method as in Examples 1 and 2.

[0114] Preparation of La-doped carbon-coated lithium manganese iron phosphate (LiMn 0.6 Fe 0.39 La 0.01PO4-S8) Positive electrode material: Weigh the masses of FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4, La(CH3COO)3·4H2O and glucose to be 11.90g, 3.37g, 13.97g, 12.63g, 0.71g and 10.65g respectively, then add 66.54mL of distilled water to mix, and ball mill at 800rpm for 12h, where the ball-to-material ratio is 15:1. Subsequently, dry at 80°C to evaporate all the water, dry mill at 1000rpm for 20min after evaporation, and sieve the powder with a 200-mesh standard sieve to obtain a precursor sample. Finally, place the precursor powder in a nitrogen atmosphere and calcine at 350°C for 4h; then calcine at 670°C for 12h to obtain LiMn 0.6 Fe 0.39 La 0.01 PO4-S8 positive electrode material.

[0115] Comparative Example 3 LiMn was prepared by the same method as in Examples 1 and 2. 0.6 Fe 0.39 La 0.01 PO4-S8 positive electrode sheets were assembled into button cells for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing process were the same as in Examples 1 and 2. The specific test results are shown in Tables 1 and 2.

[0116] After testing, it can be seen from Table 1-Table 2 that LiMn 0.6 Fe 0.39 La 0.01 The PO4-S8 positive electrode sheet has a first discharge capacity of 146.47 mAh / g at 0.1C, 141.23 mAh / g at 0.2C, 135.03 mAh / g at 0.5C, 128.82 mAh / g at 1.0C, 122.65 mAh / g at 2.0C, 113.15 mAh / g at 5.0C, and 100.59 mAh / g at 10.0C. 0.6 Fe 0.39 La 0.01 The PO4 positive electrode sheet was cycled 500 times at 5.0C, and the battery capacity retention rate was 82.25%; after cycling 500 times at 10.0C, the battery capacity retention rate was 75.67%.

[0117] The difference between the above-mentioned Example 1 and Comparative Example 3 is that: in Comparative Example 3, the hexacoordinated La 3+ The electronegativity of the six-coordinated Yb 3+The electronegativity of La is 1.479. 3+ The electronegativity of Yb is significantly weaker than that of 3+ Therefore, the weakly electronegative La 3+ For MnO6 octahedron 3+ The ability to adjust the chemical environment of the electron cloud and the effect of Mn 3+ The electron accommodation capacity of the outermost local electron cloud is weaker than that of Yb 3+ , and the suppression effect on the Jahn-Teller distortion of lithium manganese iron phosphate is weak, making the 1% La doped 3+ LiMn 0.6 Fe 0.39 La 0.01 The PO4-S8 cathode material did not show a large discharge capacity and good capacity retention rate at high rate (10.C). 3+ The ionic radius of Fe in the modified lithium manganese iron phosphate cathode material (LMFP) 2+ / 3+ , Mn 2+ / 3+ The ionic radius of La 3+ The ionic radius of Fe in the modified lithium manganese iron phosphate cathode material (LMFP) 2 + / 3+ , Mn 2+ / 3+ The ionic radius of La is about 20 pm larger. The large difference in ionic radius leads to the 0.6 Fe 0.39 La 0.01 The crystal phase of the PO4-S8 positive electrode material is unstable, and the electrochemical performance and battery cycle stability of the subsequent batteries made using this positive electrode material are poor.

[0118] Comparative Example 4

[0119] Comparative Example 4 uses Tm element instead of Yb element to prepare lithium iron manganese phosphate positive electrode material as a comparative example, the only difference is that the doping element in Example 1 is 1% Yb, while the doping element in this comparative example 4 is 1% thulium (Tm). That is, Comparative Example 4 provides a thulium (Tm) doped carbon-coated lithium iron manganese phosphate positive electrode material and its preparation method and application, and the specific process is as follows.

[0120] Preparation of FePO4 nanoparticles: In Comparative Example 4, anhydrous FePO4 nanoparticles were prepared using the same method as in Examples 1 and 2.

[0121] Preparation of Tm-doped carbon-coated lithium manganese iron phosphate (LiMn 0.6 Fe 0.39 Tm 0.01PO4-S9) Positive electrode material: Weigh the masses of FePO4 nanoparticles, Li2CO3, MnCO3, LiH2PO4, Tm(CH3COO)3·4H2O and glucose as 11.90g, 3.37g, 13.97g, 12.63g, 0.71g and 10.65g respectively, then add 66.54mL of distilled water to mix, and ball mill at 800rpm for 12h, where the ball-to-material ratio is 15:1. Subsequently, dry at 80°C to evaporate all the water, dry mill at 1000rpm for 20min after evaporation, and sieve the powder with a 200-mesh standard sieve to obtain a precursor sample. Finally, place the precursor powder in a nitrogen atmosphere, first calcine at 350°C for 4h; then calcine at 670°C for 12h to obtain LiMn 0.6 Fe 0.39 Tm 0.01 PO4-S9 positive electrode material.

[0122] Furthermore, in Comparative Example 4, LiMn 0.6 Fe 0.39 Tm 0.01 PO4-S9 positive electrode sheets were assembled into button cells for charge and discharge performance and battery cycle stability tests at different rates. The specific assembly and testing process was the same as in Examples 1 and 2.

[0123] After testing, LiMn 0.6 Fe 0.39 Tm 0.01 The PO4-S9 positive electrode sheet has a first discharge capacity of 145.28 mAh / g at 0.1C, 143.19 mAh / g at 0.2C, 140.84 mAh / g at 0.5C, 136.72 mAh / g at 1.0C, 130.94 mAh / g at 2.0C, 120.78 mAh / g at 5.0C, and 109.26 mAh / g at 10.0C. 0.6 Fe 0.39 Tm 0.01 The PO4 positive electrode sheet was cycled 500 times at 5.0C, and the battery capacity retention rate was 86.83%; after cycling 500 times at 10.0C, the battery capacity retention rate was 80.27%.

[0124] The difference between Example 1 and Comparative Example 4 is that although the six-coordinate Tm 3+ (Tm 2+ Radius 94pm, Tm 3 +Radius 86.9 pm); and Yb in the present invention 3+ (Yb 2+ Radius 93pm, Yb 3+ radius 85.8pm) have similar ionic radii, but Tm 3+ There are no unpaired single electrons (4f 12 ), is relatively stable, and has a low tendency to absorb external electrons, while the six-coordinated Yb 3+ The outer layer of the electron cloud has an unpaired single electron (4f 13 ), has a high tendency to absorb foreign electrons to achieve a stable full filling state. In other words, Yb 3+ The outermost electron layer is larger than Tm 3+ The outermost electron layer of the electrons is more inclined to absorb foreign local electrons to achieve a more stable electron layer full filling state. Therefore, the outer stable Tm 3+ For MnO6 octahedron 3+ The ability to adjust the chemical environment of the electron cloud and the effect of Mn 3+ The electron accommodation capacity of the outermost local electron cloud is weaker than that of Yb 3+ , and the inhibition of Jahn-Teller distortion of lithium manganese iron phosphate is weak, so that the 1% Tm 3 + LiMn 0.6 Fe 0.39 Tm 0.01 The PO4-S9 cathode material did not show a large discharge capacity and good capacity retention rate at high rate (10.C). In other words, doping with 1% Yb 3+ It can also reduce or inhibit LiMn 0.6 Fe 0.4-x M x The Jahn-Teller distortion of PO4 cathode material makes LiMn 0.6 Fe 0.4-x M x PO4 positive electrode material has better performance at high current density.

[0125] Table 1

[0126]

[0127] Table 2

[0128]

[0129] From Table 1-Table 2 above, it can be seen that the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01PO4-S1 positive electrode material and LiMn prepared in Example 2 0.6 Fe 0.395 Yb 0.005 PO4-S2 positive electrode material, LiMn prepared in Example 3 0.6 Fe 0.38 Yb 0.02 The rate performance of PO4-S3 cathode materials is compared, and it can be seen that the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 PO4-S1 cathode material has the best rate performance, so it can be concluded that 1% Yb 3+ The doping amount is optimal.

[0130] From Table 1-Table 2 above, it can be seen that the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 PO4-S1 positive electrode material and LiMn prepared in Comparative Example 1 0.6 Fe 0.4 Comparison of the rate performance and long cycle performance of PO4-S6 cathode materials at high rates (5.0C, 10.0C, i.e., high current density): It can be seen that the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 The rate performance and long cycle performance of the PO4-S1 cathode material at high current density are significantly better than those of the LiMn prepared in Comparative Example 1. 0.6 Fe 0.4 PO4-S6 positive electrode material, so 1% Yb 3+ The performance of the doped cathode material at high current density is better than that of the undoped Yb 3+ There is a significant improvement.

[0131] From Tables 1 and 2 above, it can be seen that the LiMn prepared in Example 5 0.6 Fe 0.39 Yb 0.01 PO4-S5 positive electrode material, and LiMn prepared in Comparative Example 2 0.6 Fe 0.4 The rate performance of PO4-S7 cathode material and the long cycle performance at high rate (5.0C, 10.0C, i.e., high current density) are compared. It can be seen that the LiMn prepared in Example 5 0.6 Fe 0.39 Yb 0.01 The rate performance and long cycle performance of PO4-S5 cathode material at high rate are significantly better than those of LiMn prepared in Comparative Example 2. 0.6 Fe 0.4PO4-S7 electrode material, so it can also be concluded that 1% Yb 3+ The performance of the electrode material after doping is better than that of undoped Yb at high current density. 3+ There is a significant improvement.

[0132] From Tables 1 and 2 above, it can be seen that the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 PO4-S1 positive electrode material, and LiMn prepared in Comparative Example 1 0.6 Fe 0.4 The PO4-S6 cathode material is compared with the rate performance and the long cycle performance at high rate (5.0C, 10.0C, high current density). It can be seen that although the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 The rate performance of PO4-S1 cathode material at low rate (0.1C-0.5C, i.e. low current density) is inferior to that of LiMn prepared in Comparative Example 1. 0.6 Fe 0.4 The rate performance of PO4-S6 electrode material is due to the Yb 3+ The ionic radius of Fe in the modified lithium manganese iron phosphate cathode material (LMFP) 2 + / 3+ , Mn 2+ / 3+ The ionic radius of Yb-doped LiMn is slightly larger, and the smaller radius mismatch leads to 0.6 Fe 0.39 Yb 0.01 The crystal structure of the PO4 cathode material changes slightly, while at low rates (0.1C-0.5C) LiMn 0.6 Fe 0.39 Yb 0.01 Mn in PO4 positive electrode material 3+ The Jahn-Teller effect is not obvious, so at this time LiMn 0.6 Fe 0.39 Yb 0.01 The properties of the PO4 cathode material itself determine its electrochemical performance, that is, LiMn without Yb doping 0.6 Fe 0.4 PO4-S1 cathode material has a higher discharge specific capacity at low current density; however, at high rates (5.0C, 10.0C, i.e., high current density), the LiMn prepared in Example 1 0.6 Fe 0.39 Yb 0.01 The discharge specific capacity and long cycle performance of PO4-S1 positive electrode material are better than those of LiMn prepared in Comparative Example 1. 0.6 Fe 0.4PO4-S6 positive electrode material, this is because LiMn 0.6 Fe 0.4 Mn in PO4-S6 cathode material 3+ The Jahn-Teller effect is significant, and Yb rare earth metal ions are doped. 3+ The outermost electron layer of MnO6 tends to absorb foreign local electrons to achieve a more stable state of half-filled or fully filled electron layer, which changes the Mn 3+ The chemical environment of the electron cloud alleviates or inhibits the LiMn 0.6 Fe 0.4-x M x Jahn-Teller distortion of PO4 cathode material, at this time, the inhibitory effect of Yb rare earth ions on the Jahn-Teller distortion effect is dominant, making LiMn 0.6 Fe 0.4-x M x PO4 positive electrode material has better performance at high current density.

[0133] From Tables 1 and 2 above, it can be seen that the LiMn prepared in Comparative Example 1 0.6 Fe 0.4 PO4-S6 positive electrode material and LiMn prepared in Comparative Example 2 0.6 Fe 0.4 The rate performance of PO4-S7 positive electrode materials is compared, and it can be seen that LiMn prepared in Comparative Example 1 0.6 Fe 0.4 The rate performance of PO4-S6 electrode material is significantly better than that of LiMn prepared in Comparative Example 2. 0.6 Fe 0.4 The PO4-S7 electrode material is attributed to the use of the highly dispersible and uniformly spherical FePO4 nanoparticles synthesized by the present invention as a precursor, so that the synthesized modified lithium manganese iron phosphate positive electrode material has more excellent electrochemical properties.

[0134] In summary, the present invention adopts an additive-free, low energy consumption, low temperature (80°C) and simple post-treatment experimental method to synthesize spherical FePO4 nanoparticles with high dispersibility, uniform particle size distribution and small particle size, and uses it as a raw material for preparing LiMn 0.6 Fe 0.4-x M x PO4 raw materials. Through the comparison of electrochemical performance, it can be seen that the LiMn 0.6 Fe 0.4- x M x PO4 positive electrode material has higher discharge specific capacity and better rate performance at high rate and high current density.3+ , Yb 3+ The unique non-spherical flexible 4f electron orbital and the outermost electron layer tend to absorb external local electrons to achieve a more stable electron layer half-filled or fully filled state to adjust the MnO6 octahedral Mn in the modified lithium manganese iron phosphate positive electrode material. 3+ The chemical environment of the electron cloud can suppress the LiMn 0.6 Fe 0.4-x M x The Jahn-Teller effect of PO4 reduces the structural distortion of the material and improves its performance.

[0135] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A modified lithium manganese iron phosphate positive electrode material, characterized in that: The modified lithium manganese iron phosphate positive electrode material is a carbon-coated modified lithium manganese iron phosphate, wherein the modified lithium manganese iron phosphate is LiMn 0.6 Fe 0.4-x M x PO4, 0.005≤x≤0.02, M is Yb or Eu.

2. The modified lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The modified lithium manganese iron phosphate has an olivine structure, Fe has a valence state of +2, and Mn and M both have a valence state of +3.

3. A method for preparing the modified lithium manganese iron phosphate positive electrode material as claimed in claim 1 or 2, characterized in that: The method comprises: Providing FePO4 nanoparticles; The solvent, the FePO4 nanoparticles, a lithium source, a manganese source, a phosphorus source, a carbon source and an M source are ball-milled to form a slurry, wherein the M source is a Yb source or a Eu source; The slurry is dried, ground and sieved to obtain powder; In an inert atmosphere, the powder is calcined in stages to obtain a modified lithium iron manganese phosphate positive electrode material, wherein the modified lithium iron manganese phosphate positive electrode material is carbon-coated modified lithium iron manganese phosphate.

4. The method according to claim 3, characterized in that The FePO4 nanoparticles are first oxidized by a divalent iron salt and a phosphorus-containing solution under oxidant conditions, and then the pH of the reaction solution is adjusted to 1.5-1.8 with an alkali solution, and the reaction is carried out for 1-3 hours to obtain a FePO4 slurry. The FePO4 slurry is calcined to obtain FePO4 nanoparticles, wherein the phosphorus-containing solution includes a phosphate solution or a phosphoric acid solution.

5. The method according to claim 3, characterized in that: The lithium source is selected from at least one of Li2CO3, LiOH, LiNO3, LiCl, and CH3COOLi; The manganese source is selected from at least one of MnCO3, Mn3(PO4)2, MnHPO4, Mn(H2PO4)2, Mn(CH3COO)2, Mn(NO3)2, MnSO4, MnC2O4, and MnCl2; The phosphorus source is selected from at least one of H3PO4, Fe3(PO4)2, FePO4, (NH4)2HPO4, NH4H2PO4, (NH4)3PO4, Li3PO4, and LiH2PO4; The carbon source is selected from at least one of glucose, sucrose, fructose, soluble starch, citric acid, amino acids, dextrin, polyvinyl pyrrolidone, and polyethylene glycol; The Yb source is selected from any one of Yb2O3, Yb(CH3COO)3·4H2O, YbCl3, Yb2(SO4)3, and Yb(NO3)3·5H2O; The Eu source is selected from any one of Eu2O3, Eu(CH3COO)3·4H2O, EuCl3, Eu2(SO4)3, and Eu(NO3)3·6H2O; The solvent is water or ethanol.

6. The method according to claim 3, characterized in that The ball milling mixing time is 6-15 hours, the rotation speed is 600-1000 rpm, and the ball-to-material ratio is 15-20:

1.

7. The method according to claim 6, characterized in that The stepwise calcination of the powder comprises: The powder is first calcined at 300-350° C. for 2-6 hours, and then calcined at 600-750° C. for 10-15 hours.

8. A positive electrode sheet, characterized in that: The positive electrode sheet is composed of a positive electrode current collector and a positive electrode slurry coated and solidified on the positive electrode current collector; The positive electrode slurry comprises the modified lithium manganese iron phosphate positive electrode material as claimed in claim 1 or 2, a conductive material, a binder and an organic solvent.

9. The positive electrode sheet according to claim 8, characterized in that: The binder is selected from any one of polyvinylidene fluoride, polystyrene butadiene copolymer, sodium carboxymethyl cellulose, polyacrylic acid, polyvinyl alcohol, polyamide, polyethylene imine, and polypyrrole; The conductive material is selected from any one of conductive carbon black, acetylene black, Ketjen black, and carbon nanotubes; The organic solvent is selected from any one of N-methylpyrrolidone, dimethylformamide and dimethyl sulfoxide.

10. A lithium ion battery, characterized in that: The lithium-ion battery adopts the positive electrode sheet as described in any one of claims 8 to 9.

Citation Information

Patent Citations

  • Method for preparing manganese phosphate lithium / carbon composite material

    CN102769131A

  • Positive electrode material of lithium ion battery and preparing method thereof

    CN103151521A

  • Nickel-doped lithium iron manganese phosphate positive electrode material as well as preparation method and application thereof

    CN114566646A

  • Preparation method of low-temperature high-dispersity spherical nano iron phosphate

    CN117023537A

  • Coated modified lithium manganese iron phosphate material as well as preparation method and application thereof

    CN117199293A

Cited By

  • Acid pickling modification method of lithium manganese iron phosphate

    CN122079106A

  • Lithium manganese iron phosphate positive electrode material and surface lithiation compensation process thereof

    CN122144691A